Monday Anomaly Manifests Adaptive Behavior. A Firm Level Evidence from Emerging Market - SHAHID, DR. MUHAMMAD NAEEM; ATEEQ, AYESHA; SATTAR, DR. ABDUL; LODHI, DR. RAB NAWAZ; ISLAM, DR. MUHAMMAD UMAR (The journal of contemporary issues in business and government, 2021)
The paper attempts to enhance the prevailing literature on AMH (Adaptive market hypothesis) and calendar anomalies by first time linking the Monday effect with Adaptive Market Hypothesis that permits the performance of well-known Monday effect to fluctuate over time. For the purpose we inspect the daily returns of 107 individual firms listed at Pakistan Stock Exchange over the period of 20 years (from January 1996 to December 2015). To explore the varying degree of return predictability of Monday effect we utilize four different subsamples comprising equal length of observations of five years each. We find return predictability of Monday effect evolves over time as performance of this effect varies from time to time and consistent with AMH. Finally, the paper suggests AMH (Adaptive Market Hypothesis) is well elucidation of behavior of Monday effect than traditional EMH (Efficient Market Hypothesis).